Utilização do óleo obtido de resíduos agroindustriais de goiaba (Psidium guajava L.) na nutrição de poedeiras comerciais - Barbosa, Nathalia Pedroso (2014)
Psidium guajava L. is a plant originated in Mexico, belonging to mytarceae family. The guava fruit is growth in economic value for the production of derivatives in the Brazilian agribusiness. However the use of guava pulp generates waste discarded in the environment, without the correct use, ie an environmental liability. The guava residue consists of pulp, peel, but mainly seeds. Yet is not described in the literature depth studies on its chemical composition or a suitable waste recovery. Thus, this study aimed to characterize the dust of organic residues of guava (donated by Food Predilecta ® - Matão, São Paulo), followed by obtaining the ethanol extract of the percolation method. The ethanol extract was characterized as the fatty acid profile, density and acid number and came to be known as: Powder oil waste processing Guava (OWG) from the OWG obtained the volatile fraction by hydrodistillation and characterization was carried out by gas chromatography coupled to mass spectrometry (GC / MS), followed by characterization of β-caryophyllene marker for high performance liquid chromatography (HPLC) and the identification of ORG constituents by GC / MS. We evaluated the antioxidant potential by free radical trapping methods 2,2-diphenyl-1- picryl hydrazyl (DPPH) and the capture of ferrous sulfate (FRAP). And finally, evaluated the implementation of the OWG, in laying hens Bovans White to verify the performance, posture, egg quality, digestibility and chemical composition of eggs and lipid oxidation of gems. The analysis of the volatile fraction of the OWG by GC / MS resulted in the identification of 25 compounds having as the major, the β-caryophyllene with 21.15%. Thus, an analytical HPLC method was revalidated in accordance with the criteria of Resolution 899/03 of ANVISA for quantification of β-caryophyllene (26.26%) in the OWG, to then be used for monitoring and characterization of OWG. Moreover, GC / MS, were identified in OWG, vitamin E and phytosterols such as α- tocopherol and the β-tocopherol, β-sitosterol and campesterol. OWG showed potential antioxidant activity, with EC50 31.24 mg / mL for the capture of DPPH and a content of 3,67.10-6 mM of ferrous sulfate per gram of capture OWG. Performance reviews and posture did not differ between treatments. The eggs of the birds supplemented with ORG and BHT had favored characteristics in relation to egg weight, yolk weight, White egg weight, suggesting the replacement of BHT, a commercial antioxidant with potential carcinogen by OWG. In supplementation in the diet digestibility analysis of OWG and BHT favored the absorption of protein and feed lipids, suggesting that because the oil antioxidant potential in preserving the laying of the power of nutritional constituents as well as to preserve the moisture content, low value caloric albumen and the lipid content in the yolks. The results showed an egg production with superior quality compared to conventional production. The work generates natural antioxidant additive application alternatives that results in improved quality, productivity and reduction in production costs. Moreover favors the export in view of the new requirements of importing countries products of Brazilian poultry.